ZEATIN INDUCED DIRECT IN VITRO SHOOT REGENERATION IN TOMATO (SOLANUM LYCOPERSICUM L.) - B. D. PAWAR,; A. S. JADHAV,; A. A. KALE,; V. P. CHIMOTE,; S. V. PAWAR, (The Bioscan, 2012)
The present investigation was undertaken to develop a highly efficient direct in vitro regeneration system, as an essential pre-requisite for the genetic transformation in tomato. Comparative studies on in vitro regeneration from cotyledon, hypocotyls and leaf explants of tomato revealed considerable variability in response to plant growth regulators. Direct shoot initiation was observed in medium supplemented with zeatin, while indirect shoot initiation with intermediate callusing phase, was observed in medium supplemented with benzylaminopurine (BAP) as cytokinin source. The MS medium supplemented with 2.0 mg/L zeatin + 0.2 mg/L indole acetic acid (IAA) was found to be the best regeneration medium with regards to regeneration efficiency, days to shoot initiation and number of shoots per explant. Among explants used cotyledons showed highest shoot regeneration efficiency (91.11%) followed by hypocotyls (87.77%) and leaf explant (85.55%). Earliest shoot initiation was observed in cotyledon explants (8.2 days), while highest numbers of shoots per explant (7.2) were obtained with hypocotyl explants. In vitro rooting initiation was observed within 14 days on MS medium devoid of any growth regulator. The in vitro rooted plantlets were successfully established in polycarbonated polyhouse with 86% survival rate.